Rosen & Barkin's 5-minute emergency medicine consult - Schaider, Jeffrey J.; Barkin, Roger M.; Hayden, Stephen R.; Wolfe, Richard E.; Barkin, Adam Z.; Shayne, Philip (Wolters Kluwer, 2020)
The sixth edition of this comprehensive yet concise Rosen & Barkin's 5 Minute Emergency Medicine Consult pulls together up-to-date and evidence-based practice guidelines for easy use in a busy emergency department. In just two brief, bullet-friendly, clutter-free pages, you can quickly decipher the information you need to confirm your diagnosis, order tests, manage treatment and more! Features new information-based on the latest practice guidelines and theoretical developments-and new approaches to diagnosis and management. Designed for integrating into your practice-in an urgent care setting with patients or during downtime between patients or meetings. Covers over 600 disease and condition topics, such as bleeding, orthopedic injuries, gastric conditions, domestic violence and more. Suitable for all practitioners, nurses and residents in an emergency room setting.